Rethoric in sport headlines in the Spanish Press - Suárez-Ramírez, Sergio; Suárez-Muñoz, Ángel (Documentación de las Ciencias de la Información, 2017)
Headlines in newspapers has been neccesary to keep the attention of readers. Nowdays even more. Digital journalism, journalism on internet, which competes with thousands of informative and advertising claims, has become a place where keep the atention is a necessity; in this area, the digital headline should be sufficiently attractive and should invite for keep the reader's attention. Today also we can find new readers. A reader who diversified his interests, ask for synthesis to attend many other occupations. Then the headlines acquires a special significance, because in many cases becomes the full new that are read, at least by busy reader. For all this we have to focus the interest in the sports cybermedia. While the sport has become a social phenomenon, it has developed as a specialized communication: the sports media. For some authors, the sport has become an inexhaustible source of news; for others, the sport is the activity that generates greater volume of information. Anyway, the sport has become one of the most successful topics for the audience. Proof of this is that the most read newspaper in Spain are sports ones.